Region-of-interest based fast transcoding for mobile video terminals - HE Qiang1; YANG Gao-bo1; ZHANG Zhao-yang3 (Tongxin xuebao)
A fast transcoding scheme based on region of interest（ROI） was proposed for mobile video terminals.According to the target displaying size,the ROIs were automatically detected from the input H.264 video stream based on visual attention model in the video server.The video stream was automatically generated at the proxy server by video transcoding for mobile terminals.Moreover,a fast mode decision algorithm was proposed for video transcoding.Experimental results demonstrate that the proposed approach can not only reduce the bandwidth occupation,but also obtain excellent video quality with a low computational complexity.